Whole Body Coordination for Self-Assistance in Locomotion - Seyfarth, André; Zhao, Guoping; Jörntell, Henrik (Frontiers in Neurorobotics, 2022)
The dynamics of the human body can be described by the accelerations and masses of the different body parts (e.g. legs, arm, trunk). These body parts can exhibit specific coordination patterns to each other. In human walking, we found that the swing leg cooperates with the upper body and the stance leg in different ways (e.g. in-phase and out-of-phase in vertical and horizontal directions, respectively). Such patterns of self-assistance found in human locomotion could be of advantage in robotics design, in the design of any assistive device for patients with movement impairments, and how it can shed light on infrastructural features of the CNS motor control. Self-assistance means that distributed parts of the body contribute to an overlay of functions that are required to solve the underlying motor task. To draw advantage of self-assisting effects, precise and balanced spatiotemporal patterns of muscle activation are necessary. We show that the necessary neural connectivity infrastructure to achieve such muscle control exists in abundance in the spinocerebellar circuitry. We discuss how these connectivity patterns of the spinal interneurons appear to be present already perinatally but also likely are learned. We also discuss the importance of these insights into whole body locomotion for the successful design of future assistive devices and the sense of control that they could ideally confer to the user.